The marine fauna of New Zealand : Pelagic calanoid copepoda Megacalanidae, Calanidae, Paracalanidae, Mecynoceridae, Eucalanidae, Spinocalanidae, Claussocalanidae - Bradford-Grieve, J. M. (NIWA (National Institute of Water and Atmospheric Research, 1994)
New Zealand Oceanographic Institute Memoir 102